Foundations of business accounting - Dodge, Roy (International Thomson Business Press, 1997)
The second edition of Foundations of Business Accounting has been fully revised and offers unrivalled coverage for students taking a first course in accounting. The text has been welcomed by students and lecturers for its thorough treatment of introductory financial accounting, combined with a much more user-friendly, interactive approach than is found in traditional accounting texts.